2018
DOI: 10.1177/1040638718779641
|View full text |Cite
|
Sign up to set email alerts
|

An improved, rapid competitive ELISA using a novel conserved 3B epitope for the detection of serum antibodies to foot-and-mouth disease virus

Abstract: The highly contagious foot-and-mouth disease virus (FMDV) afflicts cloven-hoofed animals, resulting in significant costs because of loss of trade and recovery from disease. We developed a sensitive, specific, and rapid competitive ELISA (cELISA) to detect serum antibodies to FMDV. The cELISA utilized a monoclonal blocking antibody specific for a highly conserved FMDV nonstructural 3B epitope, a recombinant mutant FMDV 3ABC coating protein, and optimized format variables including serum incubation for 90 min at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Serum samples at indicated time points were tested for the presence of antibodies against FMDV non-structural proteins (NSPs) using three commercially available competitive 3ABC Enzyme-Linked Imunosorbent Assay (cELISA) kits following the corresponding manufacturer's protocol. The three test kits were the PrioCHECK FMDV NS Antibody ELISA (Thermo Fisher Scientific) ( 47 ), VMRD FMDV Antibody Detection Kit ( 48 ), and the SERELISA FMDV NSP Antibody Competition ELISA (Zoetis Inc.). Values are cited as means ± Standard Deviations.…”
Section: Methodsmentioning
confidence: 99%
“…Serum samples at indicated time points were tested for the presence of antibodies against FMDV non-structural proteins (NSPs) using three commercially available competitive 3ABC Enzyme-Linked Imunosorbent Assay (cELISA) kits following the corresponding manufacturer's protocol. The three test kits were the PrioCHECK FMDV NS Antibody ELISA (Thermo Fisher Scientific) ( 47 ), VMRD FMDV Antibody Detection Kit ( 48 ), and the SERELISA FMDV NSP Antibody Competition ELISA (Zoetis Inc.). Values are cited as means ± Standard Deviations.…”
Section: Methodsmentioning
confidence: 99%
“…Serum samples from vaccinated cattle were evaluated 0, 14, and 21 days post-challenge for the presence of non-structural protein antibodies by commercial ELISA. None of the cattle were seropositive on the day of challenge (doc), as presented in Table 2 , confirming the DIVA compatibility of this platform using licensed diagnostic tests [ 27 , 28 ]. After challenge, only a single calf, D21-06, became seropositive, as Table 2 shows.…”
Section: Resultsmentioning
confidence: 53%
“…Moreover, relative sensitivity may be affected by different geographical location. It has previously been reported that the commercial ID Screen FMD NSP competition kit gave lower sensitivity (76.9 %) but 100 % specificity upon comparison with sera identified after virus neutralization test (VNT) and 3B ELISA [59]. Analytical specificity is also an important parameter for newly developed assays, which is determined by using sera from animals infected with clinically similar diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The detection of false positives was increased for both the in-house ELISA and the ID Screen FMD NSP competition kit in animals that had been vaccinated when compared with naïve animals. These false positive results may be associated with insufficient specificity of the assay or to the presence of 3ABC during some vaccine preparations, which should have been depleted during the manufacturing process [10,59]. It has previously been reported that animals receiving repeated local vaccination may elicit immune responses to 3ABC, which probably contributes to this observation [60].…”
Section: Discussionmentioning
confidence: 99%